Risk Avoidance In Intergenerational Investment Decisions - FADJAR, Nurman Setiawan; HASCARYANI, Tyas Danarti; PUTRI, Risqi Noor Hidayati (International Journal of Environmental, Sustainability, and Social Science, 2024)
The character of a generation also shapes risk avoidance behavior. Socio-cultural and economic background influencing each generation's character formation results in differences in the investment preferences and the risk-taking tendencies in each generation group. This research aims to observe the influence of risk avoidance behavior of intergenerational investors on their investment decisions. The sample consisted of 240 respondents, who were obtained through the distribution of research questionnaires. The primary data used in this research is data from behavioral experimental methods for each generation. They were measured, and then the levels of avoidance between generations were compared. The results prove that risk avoidance behavior in all generations results in a moderate level, with the most excellent avoidance behavior in Generation Y and Generation Z. However, if we look at the relativity of risk aversion between generations, the one with the most significant risk averter behavior is the baby boomer generation. Meanwhile, the most prominent moderate risk avoidance behavior is in Generation Y and Generation Z. The baby boomer generation tends to adopt investment behavior by avoiding existing risks compared to Generation Y and Generation Z because of the psychological differences between these four generations.